Ginger Pye - Estes, Eleanor 1906-1988. (New York Scholastic Inc., 1991)
When the Pye family's puppy, Ginger, disappears on Thanksgiving Day, the children are convinced that he has been adbucted by a stranger in a yellow hat.
An Odyssey classic.
A Newbery Medal winner--Cover.
Keywords: Dogs -- Fiction; Family life -- Fiction